Acute Exacerbation of Rheumatoid Arthritis Misdiagnosed as COVID-19: A Case Report - Torun, Serife; Karaman, Irem (Frontiers in Medicine, 2022)
Background Rheumatoid arthritis (RA) is a systemic inflammatory connective tissue disease that affects 1–2% of the population worldwide. Pulmonary manifestations including interstitial lung disease (ILD), airway disease, pleural and vascular disease can be seen in up to 30–40% of patients with RA, which are recognized as the second most frequent cause of death in RA patients. The simultaneous occurrence of COVID-19 in RA patients with or without ILD, and the similarities and differences between RA-related ILD and COVID-19 lung findings have been reported in the literature. However, there was no reported case on differentiation of clinical findings of a patient with RA exacerbation causing a new diagnosis of ILD during the pandemic conditions. Case Presentation Here, we presented a patient with RA who was misdiagnosed as COVID-19 twice due to non-specific respiratory symptoms and ground-glass opacities observed in high-resolution CT. The misdiagnosis led to a delayed diagnosis of ILD and prolonged pulmonary symptoms. Discussion Clinicians must critically review patients throughout the diagnostic workup by thinking other diseases besides COVID-19, particularly in the absence of a confirmatory result. The link between ILD or ILD exacerbation and COVID-19 remains to be determined. While research continues in the field, it is important to consider the importance of COVID-19 in cases of ILD exacerbation, and vice versa. Conclusion Distinguishing lung imaging findings of COVID-19 from ILD is a major concern. Even though the primary manifestation of COVID-19 consists of respiratory symptoms, clinicians should be vigilant for other common conditions having the same symptoms. Clinicians should carefully distinguish a differential diagnosis between COVID-19 and a flare of rheumatic disease.